HALAL PRODUCTION AT THE MEATBALL HOME INDUSTRY IN BENGKULU CITY - Miti Yarmunida; Nilda Susilawati; Khairiah Elwardah (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Abstract,Halal certification is a must in the culinary field, especially in supporting Indonesia as a world halal tourism destination. However, the phenomenon that is developing in the city of Bengkulu, there are still many processed foods, especially flour and meat such as meatballs, which are very popular with the public, do not have a halal certificate in their sales In fact, there is only 1 meatball business in Bengkulu that is registered in the 2020 LPPOM MUI halal product shopping. Thus, the purpose of this study is to describe how the process of production of food processed with flour and meat, which is mostly a category of home industry in Bengkulu City, and analyzes it using production theory in Islam. This research method is descriptive qualitative. Research informants were home industry food producers, namely food producers from processed meat and flour. This business does not yet have a brand or production permit from the related party, even though they produce the food every day and it is sold freely in the city of Bengkulu. The research instrument was an open interview guide to dig deeper into the information about the production process that the informant did. Data analysis through restatement, description and interpretation of data. The results of the study found that the meatball home industry food production process in Bengkulu City has not had a halal standard of production as regulated in production theory in Islam. This happened on the background of the lack of knowledge of home industry players about halal production and tended not to consider the issue of halal label and production permits from related parties as important.